Social customs among mothers during pregnancy in Karimnagar district, Telangana - A A Kameswar Rao; V V Sastry; A SaiRam (MRIMS Journal of Health Sciences, 2016)
Background: Customs in a community will play a key role while providing health services. Misunderstandings about these customs result in poor services. Objectives: 1) to know the various social customs practiced by mothers during pregnancy and the reasons behind them. 2. To educate the merits and demerits of these customs with the women and dais (old women who conduct deliveries in villages) as a gesture of service. Methods: A cross-sectional descriptive study in urban, urban slum and &rural settings. 150 out- patient women attending Urban and Rural health centres were enquired about the General customs, Dietary customs and Customs regarding rest, Personal hygiene& breast feeding. Results: Seemantham (bangle ceremony) was practiced by 70% urban women and only by 30% rural women. All women stayed indoors during solar eclipses. Urban mothers avoided papaya, fish, green dal and green leafy vegetables (24-92%).Rural mothers consumed special foods like Kayam, (78%) Fried jeera (60%) but less by urban mothers (22%).More urban mothers (70%) and less rural mothers (30%) commenced breastfeeding in the first day. Colostrum discarding was more (90%) among by rural mothers than among urban mothers (10%). Conclusion: Most of the customs are traditional in nature. Some are conducive to positive health while some are harmful.